SCIENTIFIC AND THEORETICAL BASIS OF TEACHING GRAMMAR BASED ON INTERACTIVE METHODS TO YOUNG LEARNERS (Web of Teachers: Inderscience Research, 2025)
The effective teaching of grammar to young learners requires approaches that align with their cognitive, emotional, and linguistic development. This paper explores the scientific and theoretical foundations supporting the use of interactive methods in grammar instruction for children. Drawing from constructivist learning theory, sociocultural theory, and second language acquisition research, the study highlights the importance of active learner participation, meaningful context, and social interaction in the learning process. Interactive techniques such as games, role-plays, storytelling, and digital tools are examined for their ability to enhance engagement, retention, and grammatical accuracy. The paper concludes that interactive grammar instruction fosters not only linguistic competence but also motivation and communicative confidence among young learners.